Spatio-temporal variation of the organic carbon stock and its relationship with changes in land use. Tandil department, Austral Pampean Region, Argentina - Somoza, Ailín; Vazquez, Patricia Susana (Revista Geográfica de América Central., 2022)
Transformations in land use are drivers of Global Change and environmental impacts associated with the provision of ecosystem services linked to the edaphic resource. The change in land use strongly affects the soil organic carbon stock, a fundamental force for soil quality and services. The objective of this work has been to estimate the variation in the soil organic carbon stock associated with the trends of the agriculturization process in the Environmental Units of the Tandil department in the period 1989 - 2004 - 2019. It was determined, in each Unit, the soil organic carbon stock using the IPCC method. The resulting data with the variation of the agricultural area in the analyzed period allowed to determine the effect of the transformations in the use of the land in each land- scape. It is evidenced that agriculturization is a key driver in the deterioration of the soil’s capacity to maintain the provision of associated ecosystem services